Clinical significance ofPseudomonas aeruginosa2‐alkyl‐4‐quinolone quorum‐sensing signal molecules for long‐term outcomes in adults with cystic fibrosis. Issue 12 (December 2019) - Webb, Karmel; Fogarty, Andrew; Barrett, David A.; Nash, Edward F.; Whitehouse, Joanna L.; Smyth, Alan R.; Stewart, Iain; Knox, Alan; Williams, Paul; Halliday, Nigel; Cámara, Miguel; Barr, Helen L.
Abstract : Introduction. : Pseudomonas aeruginosa is an important respiratory pathogen in cystic fibrosis (CF), which is associated with an accelerated decline in lung function, frequent pulmonary exacerbations and increased mortality. P. aeruginosa produces intercellular signalling molecules including 2‐alkyl‐4‐quinolones (AQs), which regulate virulence‐factor production and biofilm formation in the CF airways. Studies have shown that AQs are detectable in the sputum and plasma of adults with CF and chronic pulmonary P. aeruginosa . Aim. : We tested the hypothesis that the presence of six AQs in plasma or sputum obtained from adults with CF was associated with long‐term adverse clinical outcomes. Methodology. : We analysed clinical data over an 8 year follow period for 90 people with CF who had previously provided samples for AQ analysis at clinical stability. The primary outcome was all cause mortality or lung transplantation. Secondary outcomes were the rate of lung‐function decline and the number of intravenous (IV) antibiotic days for pulmonary exacerbations. Results. : There was no statistical association between the presence of any of the six measured AQs and the primary outcomes or the secondary outcome of decline in lung function. One of the six AQs was associated with IV antibiotic usage. The presence of 2‐nonyl‐3‐hydroxy‐4(1 h)‐quinolone (C9‐PQS) in sputum was associated with an increase in the number of IV antibiotic days in the follow‐up period (Mann‐Whitney; P =0.011). Conclusion. : Further investigation to confirm the hypothesis that C9‐PQS may be associated with increased antibiotic usage for pulmonary exacerbations is warranted as AQ‐dependent signalling is a potential future target for anti‐virulence therapies.